Anthelmintic Effect of Date Palm Fruit: A Systematic Review - Rauf, A; Addnan, FH; Manzor, NFM; Abdullah, WO; Elkadi, MA; Hamdan, F; Behnke, JM; Mansur, FAF; Khairun Nain Nor Aripin (New Century Health Publishers, Llc, 2024)
Soil-transmitted helminth infections constitute a global affliction affecting people and livestock, resulting in a significant disease burden and economic losses in endemic regions. However, control has not been entirely successful and the problem is compounded by the development of resistance to available chemotherapy. Novel alternative compounds are urgently needed, encouraging the screening of largely plant-based sources for anthelmintic effects. Date palm fruit (Phoenix dactylifera) is a popular and nutritious food much coveted for its nutraceutical effect. There are convincing reports documenting the antibacterial, antiviral and antifungal effects of date palm fruit but evidence for any potential anthelmintic effect remains unclear. Here we conducted a systematic review of the published information through an electronic search using six scientific databases; SCOPUS, MEDLINE COMPLETE, OVID, EMBASE, WEB OF SCIENCE and CINAHL COMPLETE. Out of 58 studies that were initially identified only 2 manuscripts fitted our inclusion criteria. The first article reported on the anthelmintic effect of date palm fruit against the rodent nematodes Trichuris muris and Angiostrongylus cantonensis in vitro and in vivo while the second article was based only on in vivo assessment (with coconut) of the effect on the rodent cestode Hymenolepis microstoma. Our review revealed limited anecdotal reports of the anthelmintic effect of date palm fruit against parasitic helminths, however, the majority of reports were inconclusive due to mixed results, limited focus on date palm fruit and lack of any statistical analyses. Rigorous, systematic and fully controlled studies focusing on date palm fruit are needed to validate the anecdotal evidence.